Analisis determinan harga saham perusahaan perbankan di Bursa Efek Indonesia - Keri Boru Hotang; Eindy Taufik; Ivander . (President University Press, 2022)
The purpose of this research is to examine whether audit opinion, firm size dan public accounting firm have an effect on stock prices. The population of this research is banking companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection wa carried out using a puporsive sampling of banking companies listed on the Indonesia Stock Exchange. This research used IBM SPSS software version 25. The analytical tools used in this test are classical assumption test and multiple regression. The result showed that audit opinion and firm size had a significant effect on stock prices. Yet, the public accounting firm has no significant effect on stock prices.